Distinct Role of CD11b+Ly6G−Ly6C− Myeloid-Derived Cells on the Progression of the Primary Tumor and Therapy-Associated Recurrent Brain Tumor - Sheng-Yan Wu; Chi-Shiun Chiang (Cells, 2019)
Myeloid-derived cells have been implicated as playing essential roles in cancer therapy, particularly in cancer immunotherapy. Most studies have focused on either CD11b+Ly6G+Ly6C+ granulocytic or polymorphonuclear myeloid-derived suppressor cells (G-MDSCs or PMN-MDSCs) or CD11b+Ly6G−Ly6C+ monocytic MDSCs (M-MDSCs), for which clear roles have been established. On the other hand, CD11b+Ly6G−Ly6C− myeloid-derived cells (MDCs) have been less well studied. Here, the CD11b-diphtheria toxin receptor (CD11b-DTR) transgenic mouse model was used to evaluate the role of CD11b+ myeloid-derived cells in chemotherapy for an orthotopic murine astrocytoma, ALTS1C1. Using this transgenic mouse model, two injections of diphtheria toxin (DT) could effectively deplete CD11b+Ly6G−Ly6C− MDCs while leaving CD11b+Ly6G+Ly6C+ PMN-MDSCs and CD11b+Ly6G−Ly6C+ M-MDSCs intact. Depletion of CD11b+Ly6G−Ly6C− MDCs in mice bearing ALTS1C1-tk tumors and receiving ganciclovir (GCV) prolonged the mean survival time for mice from 30.7 to 37.8 days, but not the controls, while the effectiveness of temozolomide was enhanced. Mechanistically, depletion of CD11b+Ly6G−Ly6C− MDCs blunted therapy-induced increases in tumor-associated macrophages (TAMs) and compromised therapy-elicited angiogenesis. Collectively, our findings suggest that CD11b+Ly6G−Ly6C− MDCs could be manipulated to enhance the efficacy of chemotherapy for brain tumors. However, our study also cautions that the timing of any MDC manipulation may be critical to achieve the best therapeutic result.